Dynamic mooring lines tension of FPU operated at Madura Strait. Issue 1 (August 2020) - Rahayuningsih, S; Djatmiko, E B; Handayanu,
Abstract: An FPU operated at a gas field in Madura Strait is designed to be the main process component of the gas processing facilities for a service life 20 years. This vessel using a catenary mooring system which made up of 12 points mooring divided into 4 groups of 3 mooring lines. This vessel is necessary to be analyzed its mooring tension to ensure safety while operation. The mooring line tension is analyzed by using 3D-Diffraction Calculation. This study presents the result of the dynamic mooring line tension conducted for full load condition of FPU in extreme wave condition. The mooring analysis compliance is based on DNV GL's technical standards, as well as an international accredited registrar and classification society. Verification of computed line tension against acceptance criteria has been carried out for the current condition of the mooring system. Results of the analysis indicate that mooring line tension meets the safety factor from DNVGL OS E301 with the Maximum tension of all mooring lines value is about 159.3 t, which happened in Line 4 by heading 67.5°.